Transferrin Disassociates TCR from CD3 Signaling Apparatus to Promote Metastasis - Ruomei Cheng; Xiaopeng Tang; Qiyu Zhao; Yuming Wang; Wenlin Chen; Gan Wang; Chenxi Wang; James Mwangi; Qiumin Lu; Dawit Adisu Tadese; Xudong Zhao; Caiwen Ou; et al. (Research)
Immune recognition and activation by the peptide-laden major histocompatibility complex–T cell receptor (TCR)–CD3 complex is essential for anti-tumor immunity. Tumors may escape immune surveillance by dissembling the complex. Here, we report that transferrin, which is overexpressed in patients with liver metastasis, disassociates TCR from the CD3 signaling apparatus by targeting the constant domain (CD) of T cell receptor α (TCRα), consequently suppresses T cell activation, and inhibits anti-metastatic and anti-tumor immunity. In mouse models of melanoma and lymphoma, transferrin overexpression exacerbates liver metastasis, while its knockdown, antibody, designed peptides, and CD mutation interfering with transferrin–TCRα interaction inhibit metastasis. This work reveals a novel strategy of tumor evasion of immune surveillance by blocking the coupling between TCRs and the CD3 signaling apparatus to suppress TCR activation. Given the conservation of CD and transferrin up-regulation in metastatic tumors, the strategy might be a common metastatic mechanism. Targeting transferrin–TCRα holds promise for anti-metastatic treatment.